Association between family poverty and the neuropsychomotor development of children in the administrative districts of Belém - Elson Ferreira Costa; Lilia Iêda Chaves Cavalcante; Mariane Lopes da Silva; Talitha Buenaño França Guerreiro
Abstract Introduction: Childhood development represents a sequence of changes in behavior and underlying processes, influenced by biological and environmental factors. Screening and monitoring of neurodevelopment show effective procedures for early identification of different disorders of childhood development. Objective: To analyze the neurodevelopment, using the Denver Developmental Screening Test II, of children enrolled in preschools of Administrative Districts in Belém and to map the districts and the percentage of development evaluated as normal and suspected delay. Methods: This was a cross-sectional and exploratory descriptive study. A questionnaire was administered to parents to collect the personal, contextual and family data and an instrument to measure the level of family poverty. Results: Of the 319 children assessed, 77.7% showed a suspected delay in neuropsychomotor developmental and 59.2% in language. The family poverty level variable showed a statistically significant association with the overall level of development (p = .011) and of language (p = .003). Conclusion: It is hoped that this study will contribute to generate an impact in improving the ecological conditions of children and their families, reducing the risks to which they are exposed.